Big Healthcare Data Privacy Preservation –A Technological Perspective - Suneetha, V; Suneetha, V; Srivatsala, V; Swamy Y S, Kumara (International Journal of Computer Sciences and Engineering, 2025)
In this digital world, by virtue of highly diversified data generating technologies – huge amount of data is being churned out by organizations like hospices, banks, e-commerce, retail and supply chain, etc.,. Heaps and loads of big data is being generated every minute, by humans and machines. Because of onset of big data the industries have fundamentally changes their way of handling data. The volume and velocity big data generated from the various sources can be managed and analyzed to take appropriate decisions to benefit the organization. One of the most promising fields where big data analytics can be applied is healthcare. Big healthcare data and its analytics has considerable potential to improve quality of patients’ life, gain valuable insights, prevent diseases, make healthcare more affordable. Securing data of patients and ensuring its security is major concern of data analytics. Unless the privacy and security issues of Big Data are addressed in healthcare industry it cannot be too useful. Invasion of patient privacy is a growing concern in big data analytics as emerging threats and vulnerabilities continue to grow. It is necessary to ensure a secure and sound environment for big data for better future in research by repairing the available solutions. In this paper, we present the security and privacy issues in big data applicable to healthcare industry. Also, we discuss the various Anonymization and Encryption techniques to preserve the privacy of the data, comparing their strengths and limitations.